How social movements can save democracy democratic innovations from below - Della Porta, Donatella 1956- (Polity, 2020)
Democratic innovations and social movements -- Crowd-sourced constitutionalism : social movements in the constitutional process -- Referendums from below : direct democracy and social movements -- Movement parties in the great recession -- Progressive movements and democratic innovations : some conclusions
Includes bibliographical references and index
Keywords: Soziale Bewegung; Protestbewegung; Alternativbewegung; Politische Beteiligung; Demokratie; Gesellschaft; Krise; Zukunft; Europa; Bolivien; Social movements / Political aspects; Direct democracy; Right and left (Political science)